Protective effects of paeoniflorin and albiflorin on chemotherapy-induced myelosuppression in mice - ZHU, Ying-Li; WANG, Lin-Yuan; WANG, Jing-Xia; WANG, Chun; WANG, Cheng-Long; ZHAO, Dan-Ping; WANG, Zi-Chen; ZHANG, Jian-Jun (Chinese journal of natural medicines, 2016)
Paeonia lactiflora root (baishao in Chinese) is a commonly used herb in traditional Chinese medicines (TCM). Two isomers, paeoniflorin (PF) and albiflorin (AF), are isolated from P. lactiflora. The present study aimed to investigate the protective effects of PF and AF on myelosuppression induced by chemotherapy in mice and to explore the underlying mechanisms. The mouse myelosuppression model was established by intraperitoneal (i.p.) injection of cyclophosphamide (CP, 200 mg·kg−1). The blood cell counts were performed. The thymus index and spleen index were also determined and bone morrow histological examination was performed. The levels of tumor necrosis factor-α (TNF-α) in serum and colony-stimulating factor (G-CSF) in plasma were measured by Enzyme-Linked Immunosorbent Assays (ELISA) and the serum levels of interleukin-3 (IL-3), granulocyte-macrophagecolony-stimulatingfactor (GM-CSF), and interleukin-6 (IL-6) were measured by radioimmunoassay (RIA). The levels of mRNA expression protein of IL-3, GM-CSF and G-CSF in spleen and bone marrow cells were determined respectively. PF and AF significantly increased the white blood cell (WBC) counts and reversed the atrophy of thymus. They also increased the serum levels of GM-CSF and IL-3 and the plasma level of G-CSF and reduced the level of TNF-α in serum. PF enhanced the mRNA level of IL-3 and AF enhanced the mRNA levels of GM-CSF and G-CSF in the spleen. PF and AF both increased the protein levels of GM-CSF and G-CSF in bone marrow cells. In conclusion, our results demonstrated that PF and AF promoted the recovery of bone marrow hemopoietic function in the mouse myelosuppression model.